Prediction of the voltage drop due to the diode commutation process in the excitation system of salient-pole synchronous generators - Nuzzo, Stefano; Galea, Michael; Gerada, C.; Brown, N.L. (2016)
The commutation processes in uncontrolled diode rectifiers have been extensively studied and modelled. However, in some applications, such as electrical power generation, the effects of these processes are often neglected. In low to medium rated, field wound, synchronous generators, the excitation system makes up a significant percentage of the whole generating set. Thus, the voltage drop due to the diode commutations can be quite significant. It is therefore of critical importance that these are considered during all the design stages of the brushless excitation system of synchronous generators. In this paper, a detailed analysis of the commutation aspects related to the diode rectifier of a brushless exciter of a 400kVA synchronous generator is presented and an accurate voltage drop prediction model is proposed and validated.